On the Possibility of Using Mn4N as a Neutron Polarizer - Marsongkohadi Marsongkohadi,; Kurniadi Sumaamidjaia; S. K. Paranjpe; M.R.L.N. Murthy; N.S. Satya Murthy (Journal of Mathematical and Fundamental Sciences, 1984)
Abstract. Manganese nitride, Mn4N has been investigated by means of unpolarized as well as polarized neutron diffraction technique. It was found that both (100) and (110) reflections of this compound could produce almost 100% polarized, monochromatic neutrons. Furthermore, the two reflections provide opposite senses of polarization. While (100) reflects neutrons with spins aligned opposite to the magnetization, (110) reflection provides neutrons with spins parallel to the magnetization. This would offer possibility of producing polarized, monochromatic neutrons of either state of polarization by switching from one reflection to the other, without the use of electronic flipping devices. Sari. Nitrida mangan, Mn4N telah diteliti dengan teknik difraksi neutron tak-terpolarisasi maupun terpolarisasi. Ternyata kedua refleksi, (100) dan (110), dapat menghasilkan hampir 100% neutron terpolarisasi serta monokromatik. Lebih lanjut diketahui bahwa kedua refleksi tersebut menghasilkan polarisasi yang berlawanan arah. Refleksi (100) hanya memantulkan neutron dengan polarisasi yang berlawanan arah dengan magnetisasi, sedangkan refleksi (110) menghasilkan neutron dengan polarisasi searah dengan magnetisasi. Hal ini membuka kemungkinan untuk memproduksi neutron monokromatik dengan salah satu keadaan polarisasi, dengan cara berpindah dari suatu refleksi ke refleksi lainnya tanpa menggunakan alat elektronik.